Protective Effect of Deer Heart Peptide on Cardiac Injury in Mice - Qun Zhang; Hongjin Li; Dongshu Jia; Wei Chen; Xinao Jia; Qi Lin; Jiyi Zhang; Yujiao Tang (International Journal of Inflammation)
Peptides are widely used as natural bio-small molecules because of their various pharmacological activities such as enhancing immunity, promoting wound healing, and improving inflammation. Alcoholic heart injury has become one of the major health problems worldwide, and alcohol consumption is now the main cause of alcoholic cardiomyopathy. In this study, deer heart peptides were extracted from deer hearts by enzymatic digestion and the antioxidant activity of deer heart peptides extracted at different times was evaluated by three in vitro antioxidant methods, and the active peptide with the best enzymatic effect has been selected for in vivo animal experiments. The anti-inflammatory and antioxidant properties of deer heart enzymatic extracts were evaluated in in vivo experiments in mice. In this study, mice were orally gavaged with white wine (12 mL/kg body weight) to induce a mouse model of cardiac injury, while mice were orally administered a single dose of 100 mg/kg/bw and 200 mg/kg/bw of deer heart enzyme digest and were examined for body weight, dietary intake, water intake, and coat gloss, as well as for general behaviors, adverse effects, and mortality. Histology, serum, anti-inflammatory factors, and oxidative stress parameters were subsequently assessed. In all modeled mice, no four-way or any significant behavioral changes were observed in all groups, but in the modeled group, mice showed weight loss, decreased diet and water intake, and decreased cardiac index. For in vivo tests, the extract inhibited the anti-inflammatory activity with a significant decrease in inflammatory factors of TNF-α, IL-6, and IL-1β in cardiac tissues, a significant increase in serum levels of both CAT and SOD, an increase in MDA content, and a remarkable increase in the level of the marker CK in the cardiac myocardial enzyme profile. Significant improvement in myocardial disorders by deer heart peptide could be observed from heart tissue sections. The present study emphasizes the anti-inflammatory and antioxidant activity of deer heart peptide, an enzymatic digest of deer heart, which provides empirical as well as supportive role for the anti-inflammatory properties of traditional medicine.